2005
DOI: 10.1111/j.1365-2125.2005.02573.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential in vitro inhibition of M3G and M6G formation from morphine by (R)‐ and (S)‐methadone and structurally related opioids

Abstract: Differential in vitro inhibition of M3G and M6G formation from morphine by (R)-and (S)-methadone and structurally related opioids Department of Clinical Pharmacology, Royal Adelaide Hospital, Adelaide, Australia AimsTo determine the in vitro kinetics of morphine-3-glucuronide (M3G) and morphine-6-glucuronide (M6G) formation and the inhibition potential by methadone enantiomers and structurally related opioids. MethodsM3G and M6G formation kinetics from morphine were determined using microsomes from five human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
3
7
0
Order By: Relevance
“…The reason for this discrepancy between plasma and urine is uncertain. Nevertheless, the plasma metabolic ratio data are consistent with a previous study that found both the ( R )‐ and the ( S )‐methadone enantiomers noncompetitively inhibited UGT2B7 in vitro using liver microsomes, through reducing the formation of M3G and M6G from morphine [18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The reason for this discrepancy between plasma and urine is uncertain. Nevertheless, the plasma metabolic ratio data are consistent with a previous study that found both the ( R )‐ and the ( S )‐methadone enantiomers noncompetitively inhibited UGT2B7 in vitro using liver microsomes, through reducing the formation of M3G and M6G from morphine [18].…”
Section: Discussionsupporting
confidence: 90%
“…The analgesic effect of codeine, therefore, depends on two metabolites, morphine and M6G. In the presence of methadone, however, the predominant enzyme responsible for the formation of both of these conjugated metabolites, UGT2B7 [16, 17], has been found to be noncompetitively inhibited in vitro , with the formation of M6G being more strongly inhibited than that of M3G [18]. Thus, giving morphine on its own, in the presence of methadone, may result in increased plasma morphine concentrations and reduced plasma M3G and M6G concentrations, the clinical consequences of which remain speculative.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, K i values obtained here for fluconazole (from incubations with and without BSA) of human liver microsomal COD glucuronidation were approximately 30% higher than the corresponding K i s we previously reported for inhibition of zidovudine glucuronidation (Uchaipichat et al, 2006b). K i values determined here for metha- Table 5 corrected for the predicted binding to incubation constituents (i.e., K i /fu inc ): dextropropoxyphene, 12 M; fluconazole, 220 M; ketoconazole, 7.5 M; and methadone, 0.6 M. Foster et al, 2004. done and ketoconazole inhibition of COD glucuronidation also differ from inhibition studies with the predominantly UGT2B7 substrate morphine, which reported less potent inhibition (Morrish et al, 2005;Takeda et al, 2006). While this may be caused in part by the differing contributions of UGT2B4 and UGT2B7 to COD and morphine (3-and 6-) glucuronidation and the differential inhibition of each enzyme by methadone, binding to HLM was not accounted for in the morphine inhibition studies and effects of BSA were not investigated.…”
mentioning
confidence: 81%
“…In contrast, data from both in vitro and in vivo studies indicate that inhibition of UGT2B7 may potentially result in significant drug-drug interactions (DDIs), with reduced clearance via glucuronidation. For example, DDIs in vivo have been reported between fluconazole and zidovudine (Sahai et al, 1994) and methadone and zidovudine (McCance-Katz et al, 1998), whereas dextropropoxyphene, fluconazole, ketoconazole, methadone, and valproic acid have been shown to inhibit human liver microsomal morphine or zidovudine glucuronidation (Trapnell et al, 1998;Morrish et al, 2005;Takeda et al, 2006;Uchaipichat et al, 2006b).…”
mentioning
confidence: 99%
“…The obtained drug‐specific parameters for each drug are presented in Table 2 . With respect to the Michaelis–Menten parameters, values for the formation of the two morphine glucuronides were obtained from the liver microsomes from five separate adults 25 and values for the glucuronidation of zidovudine were obtained from the liver microsomes from four adults 26 . To verify the obtained drug‐specific parameters, predictions of morphine and zidovudine clearances for 1,000 healthy adult volunteers were compared with reported clearance values in adults of 93 l/h for morphine 27 , 28 , 29 and 91.2 l/h for zidovudine 30 , 31 , 32 .…”
Section: Methodsmentioning
confidence: 99%